Vaccines and biologicals - World health Organisation, Department of vaccines and Biologicals (Geneva : WHO, Department of Vaccines and Biologicals, 2001)
This CD contains a collection of documents, resource materials and p resentations on vaccines and biologicals.
Systems requirements: Adobe Acrobat professional
Keywords: Vaccines; Biologicals